Design and development of a self-contained personal electrostatic bioaerosol sampler (PEBS) with a wire-to-wire charger. Issue 8 (3rd August 2017) - Han, Taewon T.; Thomas, Nirmala M.; Mainelis, Gediminas
ABSTRACT: Here, we present a concept of a personal electrostatic bioaerosol sampler (PEBS), which is an open channel collector consisting of a novel wire-to-wire particle charger and a collection section housing a double-sided and removable metal collection plate and two quarter-cylinder ground electrodes. The charger consists of a tungsten wire (25.4 mm long and 0.076 mm in diameter) connected to high voltage and positioned in the center of the charging section (a cylinder 50.8 mm long and 25.4 mm in diameter); a ring of stainless steel wire 0.381 mm in diameter surrounds the hot electrode at its midpoint and is grounded. The newly designed wire-to-wire charger produces lower ozone concentrations compared to traditional wire-to-plate or wire-to-cylinder charger designs. The particles captured on the collection plate are easily eluted using water or other fluids. The sampler was iteratively optimized for optimum charging and collection voltages, and collection electrode geometry. When tested with polystyrene latex particles ranging from 0.026 µm to 3.1 µm in diameter and 10 L/min collection flow rate, the sampler's collection efficiency was approximately 70%–80% at charging and collection voltages of +5.5 kV and −7 kV, respectively. The PEBS showed this collection efficiency at sampling times ranging from 10 min to 4 h. Preliminary tests with Bacillus atrophaeus bacterial cells and fungal spores of Penicillium chrysogenum showed similar collection efficiency. The use of a unique wire-to-wire charger resulted in ozone production below 10 ppb. Due to low ozone emissions, this sampler will allow maintaining desirable physiological characteristics of the collected bioaerosols, leading to a more accurate sample analysis. © 2017 American Association for Aerosol Research